EFICYENCY OF THE BALL PASSES IN THE FINALE SOCCER MATCH IN THE EUROPENA CHAMPIONSHIP ,,EURO 2008" - Bylbyl Sokoli; Fatmir Pireva; Shemsedin Vehapi (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The modern soccer has a wide variability and complexity of the technical-tactical and motoric elements during the game, which are oriented in increasing the tempo, efficiency, dynamics, attractiveness and success in competition. In this work was analyzed the sample of 27 soccer players from two national teams: the national team of Spain and the national team of Germany, the first and second ranged team in the European championship ,,EURO 2008 " With the information gathered with the ,,Castrol Performance Index" ,it was possible to express a different situational parameters in all stages of game . There were drown out the information's about the kinds and number of passes of the team and the players, the percentage of the efficiency of the team, and for each player of each team .The main issue of the work was to investigate and to describe competitive efficiency of the players and teams, respectively, competitive efficiency of the players, and the finalist teams in the last European championship, with the special focus to passes. According to the results the team of Spain in final match has as paid attention to the all kinds of ball passes. According to the form of the ball pass the team of Germany has dominated in the middle passes, train to engage the offense players with those passes .According the accuracy of pass execution, the team of Spain had the higher accuracy in short passes, which is reasonable after the goal achievement, where as prime aim was to keep the advantage in result